2017
DOI: 10.1007/s00330-017-5071-x
|View full text |Cite
|
Sign up to set email alerts
|

Whole body magnetic resonance in indolent lymphomas under watchful waiting: The time is now

Abstract: The indolent non-Hodgkin lymphomas (i-NHLs) are characterised by 'indolent' clinical behaviour with slow growth and prolonged natural history. The watchful waiting (WW) strategy is a frequently employed treatment option in these patients. This implies a strict monitoring by imaging examinations, including 18F-fluorodeoxyglucose-positron emission tomography/computed tomography (18F-FDG-PET/CT) and CT. A major concern is radiation exposure due to regularly monitoring by conventional imaging procedures. Several s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 42 publications
1
16
0
1
Order By: Relevance
“…38 MRI has been shown to be of benefit in assessing local disease and recurrent disease in other malignancy, but PET/CT may have advantages in assessing diffuse or distant disease. The heterogenicity of the lymphoma subtypes, many of which have different clinical courses, 40 as well as the varying protocols for DW-MRI also makes interpretation of the result more challenging. Firstly, we excluded studies in which paediatric patients were included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 MRI has been shown to be of benefit in assessing local disease and recurrent disease in other malignancy, but PET/CT may have advantages in assessing diffuse or distant disease. The heterogenicity of the lymphoma subtypes, many of which have different clinical courses, 40 as well as the varying protocols for DW-MRI also makes interpretation of the result more challenging. Firstly, we excluded studies in which paediatric patients were included.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exclusion of this group reduced the overall power of the study. The heterogenicity of the lymphoma subtypes, many of which have different clinical courses, 40 as well as the varying protocols for DW-MRI also makes interpretation of the result more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…However, while it is generally recognized that ADCs reflect treatment response per se, no ADC cutoff values are presently established for separating partial from complete response, which is of high clinical significance, and there is also no MRI‐based scoring system comparable to the Deauville score (ie, no reference tissue definitions). Therefore, since [ 18 F]FDG‐PET/CT is currently so well established as the imaging technique of choice for response assessment, WB‐MRI may need to establish its role in clinical situations where PET/CT is currently not recommended in clinical routine, such as in the monitoring of lymphoma patients who have achieved complete remission, or in patients with indolent NHL subtypes that undergo "watchful waiting"—a recent publication showed that WB‐MRI seems to be well suited for this task …”
Section: Lymphomamentioning
confidence: 99%
“…Without recurrent haemorrhages and concentration of haemoglobin derivatives (deoxyhaemoglobin and methaemoglobin), viscosity of the cyst remains lower and shading sign is unlikely to be observed (17). Diffusion weighted imaging is a MR sequence which provides functional information by probing the random motion of water molecules in biological tissues, also with a quantitative assessment of diffusivity calculated on the ADC map (18)(19)(20)(21)(22)(23). Endometriomas tipically show low ADC values mainly due to "T2 blackout effects", related to the low T2-weigthed signal intensity of the lesions (24).…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%